(untitled) (World Science, 2020)
There’s a global trend observed in the recent decades of increasing number of people suffering from osteoporosis. Alarming is the fact that osteoporotic fractures are one of the main causes of morbidity and mortality, especially in developed countries. The possibilities offered by physical therapy for the prevention and treatment of osteoporosis still do not have the necessary popularity among the healthcare professionals and the affected persons. The purpose of this review is to look at the options for treating and preventing osteoporosis through physical therapy. The timely and professionally conducted rehabilitation not only improves the general physical condition of affected persons, but also contributes to an increase in the psycho-emotional tone, quality of life and independence in everyday life, which are one of the important priorities of any treatment.